A Qualitative Study of Operational Excellence at a Logistics Service Provider - Kozakowska, Natalia; Täljedal, Henrik (My University, 2018)
The current state regarding the utilization of daily control and visual management, workplace organization, and continuous improvement was studied at a logistics service provider, LSP. Site visits were conducted at two geographically remote sites, LSP A and LSP B, chosen as the main research objects for the study. In addition, site visits were conducted at two other sites operated by LSP (LSP C and LSP D) and three industrial sites operated by external organizations (Companies A, B, and C). The purpose of this thesis study was to present recommendations to achieve (1) service performance predictability, (2) stability and uniformity of operations, and (3) quality ensuring improvements at an organization such as LSP, within the scope of operational excellence. An analysis of the current state and the potential areas of improvements was then conducted for the sites LSP A and LSP B on the basis of findings from the site visits and literature review. Thereafter, recommendations based on the analysis were developed and presented and conclusions were made. During the site visits, empirical data were gained by semi-structured interviews of altogether 22 interviewees. Moreover, observations were conducted at each site, based on an observer as participant approach. Theoretical data were complemented with empirical data from the site visits (e.g., existing reports and previous studies). All site visits were conducted during the early autumn of 2017. The following recommendations are primarily proposed for LSP A, and LSP B: (1) establish targets and strategies to reach the LSP vision; (2) schedule time for activities and tasks that are long-term value-adding; (3) educate and initiate bottom-up involvement of local sites as well as of operators; (4) make daily decentralized controls and follow-ups; (5) establish formal communication between shifts; (6) create a visible system for continuous improvement; and (7) create and continuously renew training documents for new employees, with best practices for organizational learning. Three conclusions were made during the study. Firstly, restrictions identified by the logistics service provider LSP are not considered as hinders for implementation of operational excellence (scarce time, budget, external ownership of site and products, and short contract periods). Secondly, there are, however, problem areas that result in negative effects on operational excellence and for these, the recommendations have been formulated. The consequential effects are low motivation, waste of time and resources, uncertainties, low effectiveness, and low transparency. Thirdly, there are direct and indirect relationships between organizational structure, systems for daily control and visual management, workplace organization, and improvement work. These relations directly affect the implementation of operational excellence initiatives.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics